RURAL WOMEN EMPOWERMENT STRATEGY IN THE DIGITAL ERA TO PROMOTE A SUSTAINABLE CREATIVE ECONOMY - Emmywati, Emmywati (LP2M Universitas Bina Bangsa, 2025)
Rural women empowerment strategies in the digital era are key to driving a sustainable creative economy. This article examines various empowerment approaches involving education, skills training, access to technology, and policy support to increase rural women's participation and contribution in the creative economy sector. This study uses qualitative methods by collecting data through in-depth interviews, participant observation, and literature studies. The results of the study indicate that rural women empowerment not only improves their economic welfare but also contributes to the social and cultural development of the community. By integrating local values ​​and global potential, this strategy is expected to create an inclusive and sustainable creative economy ecosystem.